EFFECT OF DIETARY ZINC DEFICIENCY ON THE SKELETAL MUSCLES OF MOSQUITO FISH, GAMBUSIA AFFINIS - Taneja, S K; Lath, A; Bansal, D D (Indian Journal of Fisheries, 2011)
Zinc deficiency was induced in Gambusia affinis by feeding the experimental fish on semisyntheticZn-deficient diet for 9 weeks. Their skeletal muscles were subjected to biochemical analysis and comparedwith the values of the control fish fed on Zn-supplement diet containing ZnSo4. The data revealedthat the dietary Zn-deficiency caused a reduction in DNA (25.26%), RNA (48.2%), protein (49.73%),alanine(36.8 %), aspartate(53.24 %), amino-transferases, glycogen (37.2 %), glucose-6-phosphatase (29.2 %),fructose-diphosphatase (36.02%), LDH (43.70%), acid (33.2%), alkaline (53%), phosphatases and accumulationof total lipids (42.2%), phospholipids (35.2%) and cholesterol (47.7 %) in the skeletal muscles offish.